2011
DOI: 10.1158/1535-7163.mct-11-0123
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Links Oral Cancer Progression, Pain, and Cachexia

Abstract: Cancers often cause excruciating pain and rapid weight loss, severely reducing quality of life in cancer patients. Cancer-induced pain and cachexia are often studied and treated independently, although both symptoms are strongly linked with chronic inflammation and sustained production of pro-inflammatory cytokines. Since nerve growth factor (NGF) plays a cardinal role in inflammation, and pain, and because it interacts with multiple pro-inflammatory cytokines, we hypothesized that NGF acts as a key endogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
172
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(190 citation statements)
references
References 43 publications
(79 reference statements)
9
172
0
1
Order By: Relevance
“…Increased plasma levels of leptin were identified in patients with oral premalignant lesions but not in head and neck squamous cell carcinoma (HNSCC) patients. 14,16 Significant reduction in leptin levels in OSCC patients was previously observed, and it was correlated with weight loss and cachexia status, 15,16,19 but there are controversies about this fact in the literature. 21 Our results suggested a possible involvement of serum leptin as well tissue protein expression and LepR mRNA in OSCC.…”
Section: Discussionmentioning
confidence: 97%
“…Increased plasma levels of leptin were identified in patients with oral premalignant lesions but not in head and neck squamous cell carcinoma (HNSCC) patients. 14,16 Significant reduction in leptin levels in OSCC patients was previously observed, and it was correlated with weight loss and cachexia status, 15,16,19 but there are controversies about this fact in the literature. 21 Our results suggested a possible involvement of serum leptin as well tissue protein expression and LepR mRNA in OSCC.…”
Section: Discussionmentioning
confidence: 97%
“…The pain mechanism in oral cancer can be established by association with perineural involvement, with invasion and proliferation of a cancer occurring within a nerve associated with pain. 56,57 Higher NGF levels were found in cancer tissues from oral cancer patients. 57 Angiogenesis is a crucial step in the processes of uncontrolled tumor proliferation and metastasis, and inhibiting angiogenesis is considered to be effective for treating oral cancer.…”
Section: Pathophysiology Of Oral Cancermentioning
confidence: 99%
“…56,57 Higher NGF levels were found in cancer tissues from oral cancer patients. 57 Angiogenesis is a crucial step in the processes of uncontrolled tumor proliferation and metastasis, and inhibiting angiogenesis is considered to be effective for treating oral cancer. Vascular endothelial growth factor (VEGF) is thought to be an important angiogenic factor, 58 and studies have shown that OSCC is associated with an elevated VEGF concentration in the serum.…”
Section: Pathophysiology Of Oral Cancermentioning
confidence: 99%
“…Furthermore, tumors growing in the vicinity of peripheral nerves can compromise the integrity of the nerve, inducing a neuropathic condition accompanied by persistent pain, hyperalgesia, or allodynia [29]. Other mediators that have been studied to be involved in the cancer-related pain are nerve growth hormone [30,31], bradykinin [32−34], endothelin-1 [35,36], proteases-activated receptor 2 (PAR2) [37,38], proton and acid-sensing receptor [39,40]. Carriers of the specific IL-6 (i.e.…”
Section: Pathophysiologymentioning
confidence: 99%